LONG-TERM OUTCOME OF EPIRETINAL MEMBRANE SURGERY IN YOUNG CHILDREN. Issue 3 (March 2016) - Bonnin, Sophie; Metge, Florence; Guez, Alexandra; Edelson, Catherine; Dureau, Pascal; Caputo, Georges
Abstract : Purpose: To describe the clinical characteristics of epiretinal membranes (ERMs) secondary to nonprogressive diseases in very young children and to assess their surgical outcome. Methods: Retrospective interventional case series study of 13 pediatric patients (aged less than 12 years) operated on for ERM more than a 6-year period. Visual acuity measurement, ophthalmic examination, and optical coherence tomography imaging were assessed preoperatively and postoperatively. Results: Mean age was 6.5 years (3–12 years). Mean follow-up duration was of 28.5 months (12–69 months). Among the 13 patients, there were 7 cases of idiopathic ERM, 4 cases of combined hamartoma of the retina and retinal pigment epithelium, and 2 cases of posttraumatic ERM. The diagnosis of ERM was fortuitous in 10 cases (77%). Twelve children (92%) experienced a functional improvement. All patients received adjuvant treatment of amblyopia. Best-corrected visual acuity improved significantly after surgery from 20/160 to 20/40 ( P = 0.001). Conclusion: Even in very young children, surgery resulted in a significant long-term improvement. Children screening was essential for diagnosis and treatment in most cases. Abstract : Epiretinal membrane management is mostly reported in adults. In children, epiretinal membranes are often secondary to progressive diseases but even in very young children with idiopathic membrane or epiretinal membrane secondary to nonprogressive diseases, surgery results in a significant long-term improvement.